STUDI KOMPARATIF KESTABILAN ARUS DAN TEGANGAN AKI PADA SISTEM PENGISIAN HALFWAVE DAN FULLWAVE DENGAN BEBAN PENERANGAN LED PADA SEPEDA MOTOR - M. Fadhil Dianugraha; Donny Fernandez; Rifdarmon Rifdarmon; Nuzul Hidayat (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The charging system is a vital component on motorcycles because it functions to supply electric current and recharge the battery. The 2014 Honda Supra X 125 motorcycle uses a halfwave charging system that only utilizes half the cycle of alternating current waves so that the charging current is relatively small and unstable, especially when overloaded with an LED lighting system that requires direct current. This study aims to compare the stability of current and battery voltage between halfwave and fullwave charging systems when using lighting loads, bulbs, and full LED lights. The study used an experimental quantitative approach with a pretest-posttest control group design, in which the standard charging system (halfwave) was modified to fullwave. The parameters measured include regulator voltage, battery voltage, State of Health (SOH), State of Charge (SOC), and ripple frequency at engine off and engine running conditions of 1,400 RPM. The results showed that the voltage of the fullwave regulator (13.04 V) was higher than that of the halfwave (10.84 V). In the condition of the engine running with full LED load, only the fullwave system experienced an increase in battery voltage by +1.40 V, while other combinations experienced a decrease. The SOH and SOC values in the fullwave system are more maintained, and the ripple frequency of the fullwave (maximum 45.70 Hz) is lower than that of the halfwave (maximum 84.70 Hz). It can be concluded that a fullwave charging system is more effective at maintaining current and voltage stability as well as battery life than halfwave.Keywords: Charging System, Halfwave, Fullwave, LED Light, Battery Life, Ripple